2017
DOI: 10.1111/imj.13524
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of risk assessment and overuse of computed tomography pulmonary angiography in patients with suspected pulmonary thromboembolism

Abstract: More than 50% of patients with suspected PTE may be subject to unwarranted use of CTPA in the absence of pre-test clinical prediction rules coupled with D-dimer assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
1
31
2
Order By: Relevance
“…Despite numerous guidelines and algorithms that aim to prevent overtesting with CTPA in patients at low risk of PE, there is ample evidence that CTPA is frequently inappropriately ordered ( e.g. without using pre-test clinical probability scores or ignoring evidence of low pre-test probability and/­or negative D-dimer tests) [710]. There appear to be large variations in overtesting practices between clinicians [11].…”
Section: Overtesting For Pementioning
confidence: 99%
“…Despite numerous guidelines and algorithms that aim to prevent overtesting with CTPA in patients at low risk of PE, there is ample evidence that CTPA is frequently inappropriately ordered ( e.g. without using pre-test clinical probability scores or ignoring evidence of low pre-test probability and/­or negative D-dimer tests) [710]. There appear to be large variations in overtesting practices between clinicians [11].…”
Section: Overtesting For Pementioning
confidence: 99%
“…For studies of investigations (Table ), rates of overuse (and number of corresponding studies in parentheses) comprised: 64% of coagulation tests in patients with various clinical presentations ( n = 1) 22% of thrombophilia screening tests in patients with venous thromboembolism ( n = 1) 34–62% of computed tomography scans of pulmonary arteries in suspected pulmonary thromboembolism ( n = 4) 36–40% of imaging tests in patients with low back pain ( n = 2) 54% of imaging tests in patients with abdominal pain ( n = 1) 63% of blood cultures in patients with suspected sepsis ( n = 1) 23–43% of troponin assays in patients with chest pain ( n = 2) 20% of echocardiographs in patients with various cardiac conditions ( n = 1) 17% of myocardial perfusion scans in patients with stable angina ( n = 1) 38% of referrals for telemetry monitoring in patients at risk of arrythmia 10% of liver biopsies in patients with various types of liver disease ( n = 1) …”
Section: Studies Of Inappropriate Use Of Investigationsmentioning
confidence: 99%
“…Diagnostic testing by CT pulmonary angiography (CTPA) or ventilation-perfusion scans is suggested based on clinical presentation, patient symptoms, d-dimer test and pre-test probability. However, multiple prior studies have raised a concern about overutilisation of CTPA and non-adherence to the use of clinical probability scores 3 4. The trends towards the use of CTPA is on the rise, with usage greater than 10 times over the last decade 5…”
Section: Introductionmentioning
confidence: 99%
“…The positive yield of CTPA has varied extensively with most studies showing a yield of between 6%6 and 34% 3 7. However, a more recent study found a CTPA positive yield of <1% (0.2%) in a tertiary care centre in the USA.…”
Section: Introductionmentioning
confidence: 99%